The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.eneco.2013.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Renewables in the energy transition: Evidence on solar home systems and lighting fuel choice in Kenya

Abstract: We study the determinants of households' choices of lighting fuels in Kenya, including the option of using solar home systems (SHSs). The paper adds new evidence on the factors that influence the introduction and adoption of decentralized and less carbon-intensive energy sources in developing countries. We capitalize on a unique representative survey on energy use and sources from Kenya, one of the few relatively well-established SHSs markets in the world. Our results reveal some very interesting patterns in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 21 publications
5
53
0
Order By: Relevance
“…The author incorporated this barrier in terms of high total cost, high up-front price, and payment inflexibility. In line with Pode [36], Lay et al [40] identified the low income level of households to be a barrier for the adoption of SHS in Kenya. Moreover, a study by Komatsu et al [37] indicated that income alone cannot explain the SHS adoption in Bangladesh.…”
Section: Economic Barriersmentioning
confidence: 87%
See 2 more Smart Citations
“…The author incorporated this barrier in terms of high total cost, high up-front price, and payment inflexibility. In line with Pode [36], Lay et al [40] identified the low income level of households to be a barrier for the adoption of SHS in Kenya. Moreover, a study by Komatsu et al [37] indicated that income alone cannot explain the SHS adoption in Bangladesh.…”
Section: Economic Barriersmentioning
confidence: 87%
“…This was observed by Bawakyillenuo [39], who analyzed the case of Ghana in comparison with Kenya and Zimbabwe. However, Lay et al [40] found that grid extension does not necessarily prevent the adoption of SHS in Kenya. This is because SHS can be sometimes considered as a complementary energy source.…”
Section: Policy Barriersmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, it would seem logical that their influence on promoting knowledge sharing would gradually be reduced when competition in the local industry increases. With regard to explanations highlighting the growing middle class in Kenya, further research may also analyse in greater detail the importance of income relative to other influential factors, such as level of education, awareness and so-called neighbor effects (see Lay et al [76]). …”
Section: Crosscutting Discussion Of Findings and Gaps In The Literaturementioning
confidence: 99%
“…However, such decarbonization of energy systems is linked to very high incomes. A recent analysis of Kenyan households' lighting fuel choices, which suggests that while there is a cross--sectional energy ladder, the income threshold for modern fuel use -including solar energy use -is very high (Lay et al 2012). Furthermore, scaling up low carbon energy--supply to a level needed beyond fulfilling basic needs is rather difficult and would probably impose additional costs on developing countries .…”
Section: Challenges To Energy System Transformation In Developinmentioning
confidence: 99%